Spatial Heterogeneity Impacts of Bilateral Foreign Direct Investment on Green Energy Efficiency in China - Ma, Guangcheng; Cao, Jianhua (Frontiers in Environmental Science, 2022)
At present, green energy transformation and climate policy are increasingly connected. The need to improve national competitiveness and implement climate and energy strategies means that an energy-consuming country like China must rapidly enhance its green energy efficiency (GEE) and energy consumption structure. The following paper contributes to the existing literature by analyzing the effects of bilateral FDI on GEE from the perspective of spatial correlation. Based on data from 30 Chinese provinces between 2003 and 2020, this paper uses multiple undesired output indicators covering eight pollutants to measure GEE and then uses the coupling function to measure the coordinated development level of bilateral FDI (CDFDI). According to the Panel Vector Autoregression model, there is a coupling relationship between bilateral FDI. Both the global Moran index and the local Moran scatter plot show that GEE and CDFDI are characterized by spatial aggregation. This paper adopts the dynamic Spatial Dubin Model for empirical analysis. Our results reveal a significant positive impact of CDFDI on GEE in local and nearby regions. The impact of CDFDI on GEE is moderated by technological diffusion, nationalization, and environmental regulation, resulting in differential impacts on GEE in local and nearby regions. Furthermore, CDFDI with different investment motives has a boosting effect on local GEE. Among them, the mutual investment portfolio between China and developed countries has a negative impact on the local GEE. By contrast, the complementary investment motivation portfolio can boost GEE in local and adjoining regions in any period. This is the first paper to study the spatial effects of green energy efficiency and the heterogeneity of investment incentives to help Chinese international investment policymakers better understand the contribution of CDFDI to improving GEE and inform supportive policies. To improve green energy efficiency, the government must strengthen the implementation of the opening-up policy and create international capital flows suitable for local needs.